KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK DAN PROFESIONAL GURU SEKOLAH MENENGAH PERTAMA DI ACEH BARAT - Rosita, Rosita; Bahri, Saiful; Mulyadi, Said (Hijri, 2023)
This research was carried out with the educational management problems that are being faced by several junior high schools in West Aceh Regency consisting of various types of problems that can be seen from school institutions, teaching staff and educational staff. The aim is to improve teacher human resources so that they can increase students' understanding. This research was carried out at SMP Negeri 1 Meulaboh and SMP Negeri 3 Meulaboh with the research subjects being the principal, deputy principal and teacher council. The approach used in this research is a qualitative approach using descriptive. Data collection from research subjects was carried out through observation, interviews and documentation. The principal's leadership style is to provide direction to follow the programs needed to improve teacher competency, control teachers, provide direction, protect teachers and provide sanctions if they violate. Meanwhile, the principal's strategy to improve teacher professional competence and teacher pedagogical competence is by placing teachers to participate in all teacher competency programs compulsorily. For supporting factors, there is support from programs from the department and government in improving teacher competency such as the MGMP program, education and training, and teacher training. This is different from the inhibiting factors where there are facilities and infrastructure and a lack of teacher motivation in improving competence.